Internship Experience: TBL and Cooperative Learning (2025)
This internship was carried out at the Camilo Torres Educational Institution through the Bilingualism for Peace program. This internship had the objective to improve the reading comprehension of Elementary Level students. Furthermore, this internship helped me explore and improve my teaching methods and realize that as a teacher I not only teach English in terms of grammar, but other subjects can also be taught within it. This paper describes the program where the internship took place, the pedagogies implemented, the methodology, the results, conclusions, recommendations and limitations of this significant process in which I had not only professional but also personal growth .